Research progress on dynamic recrystallization behavior of Al-Li alloy - GUO Youjie; LI Jinfeng; LIU Danyang; ZENG Zhuoran; YAN Yuanming; WANG Yuan; QIU Yao; ZHANG Ruifeng (Journal of Aeronautical Materials, 2022)
Al-Li alloy has been widely used in aerospace field attribute to the advantages of lower density, higher strength, damage tolerance and corrosion resistance. Dynamic recrystallization phenomena exist in Al-Li alloy during hot deformation. This paper overviews the dynamic recrystallization behavior occurring in hot processing of Al-Li alloy. The research history of dynamic recrystallization is summarized, together with the key factors that influencing the dynamic recrystallization processes including stacking fault energy, grain size, hot processing conditions and secondary particles. The nucleation mechanisms and conditions of discontinuous dynamic recrystallization, continuous dynamic recrystallization and geometric dynamic recrystallization are depicted and analyzed respectively, followed by a discussion on the effects of the forward three dynamic recrystallization mechanisms regarding the mechanical properties and microstructure. Ultimately, the unsolved and challenging scientific and technological issues are highlighted with some aspects desiring further exploration. It is feasible to provide ideas and inspiration for scholars to better comprehend dynamic recrystallization mechanisms during the hot deformation of Al-Li alloy with the assistance of electron backscatter diffraction and transmission electron microscopy characterization methods.